IMPLEMENTASI BOARDING SCHOOL UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK MADRASAH TSANAWIYAH SATU ATAP AL HIKAM CENDEKIA KECAMATAN KALIKAJAR KABUPATEN WONOSOBO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This research aims to determine: First, the implementation of Boarding School which includes planning, implementation, monitoring, evaluation and follow-up to achieve the goal in Madrasah Tsanawiyah Satu Atap Al Hikam Cendekia Kalikajar District of Wonosobo regency, Second, the relation of  Boarding School with efforts to improve the learners' learning achievements of Madrasah Tsanawiyah Satu Atap Al Hikam Cendekia Kalikajar District of Wonosobo regency, and third, supporting factors and inhibiting factors of Boarding School Action Reviews in order to improve the learning achievement of students in Madrasah Tsanawiyah Satu Atap Al Hikam Cendekia Kalikajar Distric of Wonosobo regency .The research was conducted using qualitative approach, because the main purpose is to illustrate the implications of Boarding School to improve student learning achievement Madrasah Tsanawiyah Satu Atap Al Hikam Cendekia Kalikajar District of Wonosobo regency. The data sources were collected directly by researcher , analyzed inductively, while the research result are analyzed in the discriptive form in an enterpretation. The research is carried out in four steps: pre field step, while field step, data analizing step, and report composing step.Research results showed, first,  that the Boarding School implementation wich includes the planning, the implementation, the monitoring, the evaluation and the follow-up to achieve the goal in Madrasah Tsanawiyah Satu Atap Al Hikam Cendekia Kalikajar District of Wonosobo regency is good , second, there are a correlation between the Boarding School with the effort to improve the achievements of Madrasah Tsanawiyah Satu Atap Al Hikam Cendekia Kalikajar District of Wonosobo regency students, and  third , there are supporting factors  and  inhibiting  factors  in the implementataion of Boarding  School  in order to improve the achievement of Madrasah Tsanawiyah Satu Atap Al Hikam Cendekia Kalikajar District of Wonosobo regency students.